Surgical excision of abscess in rabbit (Oryctolagus cuniculus): Case report - Santos, Stephane; Bessa, Larissa; Francisco Costa Solak, Thiago; monteiro, sharlenne; Basilio Roberto, Gabriela (Pubvet, 2021)
An adult male rabbit (Oryctolagus cuniculus), weighing 3.3 kg, presenting a firm looking mass located in the ventral thoracic region, apparent bite wounds in the same region and history of recent fight with another rabbit, received veterinary medical attention. The initial clinical suspicion was subcutaneous abscess, based on the anamnesis and physical examination, and it was confirmed through cytological examination. The treatment was surgical, using the marsupialization technique. After ten days postoperatively, it was found that this treatment did not achieve satisfactory results, because there was no reduction of the abscess. Therefore, it was decided to perform a surgical excision of the abscess. This second treatment had satisfactory results, as it was possible to completely remove the abscess and there was no recurrence. The patient was discharged after fifteen days. Based on the literature and our observations of the case described here, we conclude that surgical excision is the most suitable treatment for subcutaneous abscesses in rabbits. The abscess marsupialization surgery was not effective due to the extent and location of the abscess, and this technique is recommended for cases in which the abscess is deeply attached to subcutaneous structures and its complete excision is not possible, and when it is located in the perineal region or at the base of the ear, otherwise there are great chances of recurrence and treatment failure.